Penguatan Nial-Nilai Moderasi Melalui Konsep Islam Rahmatan Lil Alamin di Era Four Point Zero - Hosaini, Hosaini; Ni'am, Syamsun; Mahtum, Rohiqi (Proceedings of Annual Conference for Muslim Scholars, 2023)
This research aims to increase the values ​​of Moderation in an effort to establish the principle of religious tolerance as a good national and state commitment in the real world and on social media. Using narrative-based descriptive qualitative methods. To foster a spirit of unity to become a developed country from various aspects, requires a spirit of nationalism and patriotism. Thus, society must be equipped with the Islamic concept of Rahmatan lil Alamin as an effort to form the principles of a tolerant society in everyday life and on social media.Conclusion: The Islamic concept of Rahmatan lil alamin is very effective in forming the character of a moderate and tolerant society between religious communities, supported by 4 moderate attitudes, namely, first, moderate towards the world of the afterlife, second, moderate towards fanaticism, third, moderate prejudice, good and bad, fourth, moderate optimism and psychism.